ANECDOTES AS AN INSTRUMENT OF ISLAMIC RELIGIOUS EDUCATION ASSESSMENT OF AFFECTIVE ABILITIES OF STATE ELEMENTARY - Ridha Aulia; Rasyidah Ratna Putri; Anwar Musaddad; Zarkasi Efendi; Lalu Kholid Jaelani (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
Non-test assessment is very important to do, especially for effective assessment of students. Affective assessment is closely related to the attitude of students, one of the affective domain assessment instruments that can be used is anecdotal records. The research method used in this study uses a qualitative research approach through case studies, the research method centers on adjusting aspects of affective assessment including receiving, responding, assessing, organizing, and characterizing. The results showed that in the implementation of the anecdotal note instrument based on teacher observation observations were only limited to what was seen in the classroom and the school environment, the affective abilities of students slowly increased along with the level and were also supported by the results of teacher reports.